Expression Analysis of Proline Metabolism-Related Genes in Salt-Tolerant Soybean Mutant Plants - Ünsal, Selin Gül; ÇELİK, ÖZGE (Southern Cross Publ, 8 91-93 Mckenzie St, Lismore, Nsw 2480, Australia, 2013)
Salt stress is one of the important abiotic stress factors. Proline is generally thought to play an important role in the improvement of salt tolerance in plants. In the present study, we discussed the relationship between free proline accumulation and the expression patterns of the genes that play roles in proline metabolism (P5CS, P5CR, PDH, P5CDH) under 90 mM NaCl stress. We used three salt tolerant M3 generation soybean mutant plants (Ataem-7/150-68, S04-05/150-2 and S04-05/150-114). The mutants belonging to M3 generation are determined as tolerant to 90 mM NaCl. The free proline contents of the salt-tolerant mutants were measured at the upper phase of the extract with respect to toluene. We observed 1.96-, 2.43- and 1.14-fold increases in the free proline accumulation of Ataem-7/150-68, S04-05/150-2 and S04-05/150-114 mutant plants after 7 days of salt treatment in accordance with control groups, respectively. The expression analyses were performed using specific primers designed for soybean gene regions. According to the results of the quantitative reverse-transcriptase polymerase chain reaction, all the genes were up-regulated when these mutants were subjected to salt stress. In addition to increased expression levels of these genes in three salt tolerant soybean mutants, the only statistically significant relation was observed between the regulation of P5CR and PDH gene expressions and proline content in S04-05/150-114 mutant. In further studies, the other possible mechanisms that cause proline accumulation should be evaluated for these salt tolerant soybean mutants.
Keywords: soybean mutants; proline metabolism-related genes; qRT-PCR; antioxidative enzymes; tomato plants; stress; biosynthesis; salinity; accumulation; rice; degradation; cultivars; increases; soya fasulyesi mutantları; prolin metabolizması ile ilgili genler; antioksidan enzimler; domates bitkileri; stres; biyosentezi; tuzluluk; birikim; pirinç; bozulma; artışlar